The Trace of Hinduism and Buddhism in Si Sa Ket Province, Before 23 Buddhist Centuries - หิรัญบูรณะ กวินวัฒน์ (Journal of Humanities and Social Sciences, Rajapruk University, 2020)
Human and Religion are bond together from past to present. Si sa ket is one of the long living territories. So religions are the reflections of human thought. From the study, there are 2 periods of the traces of religions in Si sa ket. First period is in the 16 - 17 Buddhist centuries, Si sa ket territory was under the influenced of Ancient Khmer Kingdom. There was a Hinduism trace in architecture and sculpture that was found. The second period is in 18-22 Buddhist centuries, under the reign of King Jayavarman VII, he changed his religion to Mahayana Buddhism which changed the religious place all over his kingdom, along with the construction of hospital in Si sa ket. Until 21-22 Buddhist centuries, there was a changing of the ancient khmer stone sanctuaries into Lao art pagoda.